What's missing? Diagnostic workup for breast cancer in Sudan. Issue 28 (1st October 2022) - Eltoum, Noon; Caston, Nicole E.; Gutnik, Lily; Alfardous Alazm, Mahmoud A.; Mohamed, Feras Omer; Abdalkarem, Lama Mahjoub; Saad, Saad Ahmed; Badawi, Abrar Z.; Henderson, Nicole; Azuero, Andres; Rocque, Gabrielle Betty
Abstract : 110 Background: In Sudan, healthcare access may limit diagnostic workup for breast cancer. This study evaluates the relationship between geography and ethnicity and completeness of documentation of diagnostic workup (staging and receptor testing) in Sudan. Methods: This retrospective study used data abstracted from patients with breast cancer receiving cancer care at Sudan's largest cancer center (Radiation and Isotopes Center Khartoum [RICK]) in 2017. The patient's age at diagnosis, sex, breast cancer stage, ethnic subgroup (further categorized as Arab and non-Arab), regions of origin and residence (Central, Northeastern, Western, and Khartoum [where RICK is located]), and receptor status from pathology reports were abstracted from paper medical records. Complete diagnostic workup was defined as having both receptor testing and staging. Descriptive statistics were calculated using frequencies and percentages for categorical variables and median and interquartile range (IQR) for continuous variables. Odds ratios (OR) and 95% confidence intervals (CI) were estimated to evaluate complete diagnostic workup on ethnic group, origin, and residence using binomial logistic regression models (excluding non-Sudanese patients and those with missing demographics). Results: Of 240 patients included, 237 were female, median age was 53 (IQR 43-62). Most often patients were Arab (68%), originated from Northeastern and Khartoum regions (both 28%) and lived in the Khartoum region (53%). Overall, 49% patients were missing receptor testing and/or staging, with modest differences by geographic region and ethnicity (Table). In adjusted analyses, non-Arab patients had similar odds of having complete diagnostic workup when compared to Arab patients (OR 1.22; 95% CI 0.70-2.10). Patients originating from and residing in regions outside the Khartoum region had similar odds of complete diagnostic workup when compared to patients originating from and residing in the Khartoum region. Conclusions: Almost half of breast cancer patients had incomplete diagnostic workup, regardless of region of origin, region of residence, and ethnic group. This highlights a substantial systems-based quality gap in care delivery, warranting efforts to improve completeness in diagnostic workup for all patients with breast cancer in Sudan.Demographic characteristics (N = 240). Both Available % n = 123 Missing Receptor Testing % n = 48 Missing Staging % n = 51 Both Missing % n = 18 Total Ethnic Group Arab Arab 50 20 22 9 68 Non-Arab Beja 57 43 0 0 3 Darfurian 56 11 22 11 8 Hausa/Fulani 38 50 13 0 3 Nuba 50 25 25 0 2 Nubian 58 15 23 5 17 Geographic Origin Central 44 23 26 8 28 Khartoum 56 21 21 3 28 Northeastern 54 18 21 7 28 Western 51 18 15 15 16 Geographic Residence Central 44 22 26 9 19 Khartoum 29 20 21 2 53 Northeastern 51 20 20 9 19 Western 44 17 17 22 10 *Non-Sudanese patients and patients with missing data for demographics were excluded.